Covid era and online payment systems in India - Chauhan Saraswati; Singh N.P. (Industrija)
Research article presents the online payment systems in India and the impact of Covid on Indian economy, role of financial technologies in facilitating financial transaction for citizens and institutions, and initiatives taken by Reserve Bank of India in the form of creating new digitally embedded organization so that reliance on banking systems is eased and industries (e.g., MSME), entrepreneurs, and citizens can get credit without much of manual paper work. In addition, the research article analyzed changes in consumer behavior as a result of the pandemic and digital technology in daily life. For the discussion and results, secondary data is collected from various sources, including websites, portals, annual reports, blogs and write-ups, and so on. The research approach used in this study is exploratory and descriptive, which analyze the various online payment or financial technologies adopted and used by different financial companies, including Indian banks. Finding of the study reveals the expansion of technological infrastructure and the adaptation to new developments in India. In addition, researchers have also explored the process of the issuance of new licenses to new categories of financial organizations, i.e., establishment of payment banks, trade receivables discounting systems (TReDs), peer-to-peer platforms, regulatory frameworks for account aggregators (AA) and NBFC-AA, establishment of wholly digital loan firms (NBFCs), etc.